The Oblivious Organization: Understanding Racial Stereotypes in the Public Sector - Nicole Humphrey; Shannon Portillo; Domonic Bearfield; Alesha Doan (Journal of Social Equity and Public Administration)
Organizational obliviousness is a theoretical framework that acknowledges how socially constructed stereotypes of marginalized groups become embedded individually, culturally, and institutionally within organizations. Prior work on organizational obliviousness has focused on exploring gender within organizational contexts. This work builds on previous scholarship on organizational obliviousness in the public sector and discussions of race in public organizations. It also builds on applying the organizational obliviousness framework in order to understand how racialized and intersectional forms of oppression manifest within public organizations. Specifically, we use the organizational obliviousness framework to explore how grooming and appearance policies that seem neutral on the surface can be exclusionary and grounded in racial stereotypes.